Antimicrobial graphene-based coatings for biomedical implant applications - Jesus Romo-Rico; Richard Bright; Smriti Murali Krishna; Krasimir Vasilev; Jonathan Golledge; Mohan V. Jacob (Carbon Trends, 2023)
Implant-associated infections (IAI) cause significant health issues and healthcare costs. In this research, we deposited graphene (Gr) on a medical-grade cobalt-chromium (CoCr) alloy surface by radiofrequency plasma-enhanced chemical vapor deposition (RF-PECVD) using Origanum vulgare as a precursor material. The deposition of Gr on the CoCr was confirmed using Raman spectroscopy and X-Ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). The biocompatibility and antibacterial properties of CoCr-Gr were investigated. CoCr-Gr was biocompatible and promoted cell adhesion and spreading of RAW 267.4 macrophage cells. CoCr-Gr were antibacterial against Staphylococcus aureus and Pseudomonas aeruginosa and inhibited P. aeruginosa attachment. The results indicate that CoCr-Gr could be used as a potential antibacterial coating material for implantable devices.